Sacred place and sacred time in the Medieval Islamic Middle East : a historical perspective - Talmon-Heller, Daniella (Edinburgh studies in classical Islamic history and culture., 2020)
This book offers a fresh perspective on religious culture in the medieval Middle East. It investigates the ways Muslims thought about and practiced at sacred spaces and in sacred times through two detailed case studies: the shrines in honour of the head of al-Husayn (the martyred grandson of the Prophet), and the holy month of Rajab.